2013
DOI: 10.1111/1471-0528.12406
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and vomiting in pregnancy: associations with maternal gestational diet and lifestyle factors in the Norwegian Mother and Child Cohort Study

Abstract: Objective To investigate primarily the dietary intake, as well as demographics and selected lifestyle factors, of women experiencing nausea and vomiting in pregnancy, nausea only, or women who are symptom free.Design Prospective cohort study.Setting The Norwegian Mother and Child Cohort Study, a population-based pregnancy cohort.Sample Analyses were based on 51 675 Norwegian pregnancies.Methods Dietary intake was assessed by a self-reported food frequency questionnaire answered in the first trimester of pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 48 publications
(45 reference statements)
10
65
0
3
Order By: Relevance
“…Three previous studies examined the effects of NVP on food intake using cross‐sectional data, two in Scandinavia (Latva‐Pukkila et al, 2010; Chortatos et al, 2013) and one ecological study based on international data (Pepper & Craig Roberts, 2006). There is little consistency in the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three previous studies examined the effects of NVP on food intake using cross‐sectional data, two in Scandinavia (Latva‐Pukkila et al, 2010; Chortatos et al, 2013) and one ecological study based on international data (Pepper & Craig Roberts, 2006). There is little consistency in the findings.…”
Section: Discussionmentioning
confidence: 99%
“…The limited cross‐sectional evidence comparing NVP and reported dietary intakes reveals inconsistent associations. In a recent Norwegian study (Chortatos et al, 2013), women with NVP had slightly higher intakes of fruit and vegetables and more noticeably higher intakes of sugar‐containing soft drinks than other pregnant women. In a smaller Finnish study (Latva‐Pukkila, Isolauri, & Laitinen, 2010) women with NVP ate less meat and somewhat fewer vegetables than other pregnant women, whereas an ecological study across 21 countries (Pepper & Craig Roberts, 2006) suggested that high rates of NVP are associated with high intakes of meat, milk and eggs, and low intakes of cereals and pulses.…”
Section: Introductionmentioning
confidence: 94%
“…6,11 Hormones associated with pregnancy and possibly NVP and HG include hCG, thyroxine, progesterone and oestrogen but psychological, genetic and external risk factors such as smoking, age, infection and diet are also implicated. 2,16,[17][18][19][20][21][22] Discretionally, these implicated causes are hereby briefly reviewed under five basic points:…”
Section: Nausea and Vomiting In Pregnancy And Hyperemesis Gravidarummentioning
confidence: 99%
“…37 Young women appear to have increased severity and incidence of NVP. 2 Weigel and Weigel, reported that women over 35 years had comparatively low rates of NVP while pregnant adolescents had high rates of NVP. 38 It has been postulated that adolescent women had a stronger anabolic drive hence a poorer outcome of pregnancy than older women.…”
Section: External Factorsmentioning
confidence: 99%
See 1 more Smart Citation